The legalization of human rights : multidisciplinary perspectives on human rights and human rights law - Meckled-García, Saladin, 1968-; Cali, Başak, 1974- (Routledge, 2006)
This book explores the problematic relationship between human rights and their legal expression. Using a multidisciplinary approach, the authors scrutinise the extent to which legalisation shapes the human rights ideal, and survey the ethical,